2015
DOI: 10.1021/acs.macromol.5b00757
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrogen Bonding on Linear and Nonlinear Rheology of Entangled Polymer Melts

Abstract: Supramolecular polymers are used in many applications such as adhesives, coatings, cosmetics, and printing. Characterizing the dynamics of such polymers is essential for tailoring user defined properties in products and applications. We present both linear and nonlinear rheological results for a model system of pure poly(n-butyl acrylate), PnBA, homopolymer and four PnBA-poly(acrylic acid), PnBA-PAA, copolymers with different number of AA side groups. The copolymers are synthesized via hydrolysis of the pure P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
146
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(166 citation statements)
references
References 27 publications
20
146
0
Order By: Relevance
“…Both the loss modulus and the storage modulus of P3, P4 and P5 against the angular frequency are nearly parallel; but both moduli do not follow the power law with the frequency. This behaviour is similar to the previous report on the rheology behaviour of the poly(n-butyl acrylate) and poly(n-butyl acrylate)-co-poly(acrylic acid) by Shabbir et al 49 Figure 8c gives the strain-time curve of P3 to test the mechanical elasticity at 25 o C.…”
Section: Mechanical Properties Of Multiblock Elastomerssupporting
confidence: 90%
“…Both the loss modulus and the storage modulus of P3, P4 and P5 against the angular frequency are nearly parallel; but both moduli do not follow the power law with the frequency. This behaviour is similar to the previous report on the rheology behaviour of the poly(n-butyl acrylate) and poly(n-butyl acrylate)-co-poly(acrylic acid) by Shabbir et al 49 Figure 8c gives the strain-time curve of P3 to test the mechanical elasticity at 25 o C.…”
Section: Mechanical Properties Of Multiblock Elastomerssupporting
confidence: 90%
“…However, measurements of molecular mass distributions performed by size-exclusion chromatography show that the polydispersity indexes (PDI = M w /M n ) are similar in value for sodium carboxymethylcellulose used in the studies (for DS 0.62; 0.79 and 1.04, they are equal to 2.09 (M w = 264,400 g/mol); 1.95 (M w = 242,200 g/mol) and 1.83 (M w = 262,400 g/mol), respectively). This shows that differences in the scaling exponents for the Na-CMC solutions with varying DS will be related to interactions between the polymer macromolecules (Lewis et al 2014;Shabbir et al 2015). Xiquan et al (1990) demonstrated in X-ray diffraction experiments that in the sodium carboxymethylcellulose aqueous solution for DS B0.82 the derivative crystalline regions are present, i.e.…”
Section: Dynamic Rheological Propertiesmentioning
confidence: 94%
“…This observation has been previously observed in LVE of several hydrogen bonding associating polymers. 6,11,12,31,32 This could be due to either, (i) the relatively large PDI of the polymer, (ii) the polydispersity in UPy side group spacing along the backbone, or (iii) the signature response of hydrogen bonding polymers. Although concrete evidence is lacking, we hypothesize that the lack of a terminal response is most likely due to (ii), the polydisperse UPy side group spacing along the backbone.…”
Section: Linear Viscoelasticitymentioning
confidence: 99%
“…In general there are three effects of increasing interaction strength and number of associations per chain on linear viscoelasticity: (i) the longest relaxation time increases, (ii) the plateau modulus increases, and (iii) the power law scaling in the terminal regime deviates towards lower magnitudes. 6 Seiffert hypothesizes that (iii) is predominately due to polydispersity in the dispersion of associating groups along the backbone and not polydispersity in polymer molecular weight. 44 Figure 10a, which has no hydrogen bonding groups present, the discrepency between experiment and model is hypothesized to be explicitly due to effects of polydispersity in molecular weight.…”
mentioning
confidence: 99%